Caracterização da textura de superfície relacionada à segurança ao tráfego em rodovias federais de Sergipe - Bomfim, Thaynná Almeida dos Santos (2024)
The tire-pavement adherence is a key factor for traffic safety. Surface texture and wheel track rutting directly influence this adherence. Surface texture, comprising microtexture and macrotexture, plays a crucial role in tire-pavement friction, especially in wet conditions and speeds over 50 km/h. This study evaluated the conditions of federal highways in the state of Sergipe by conducting tests at 75 points on BR-101 and BR-235, assessing macrotexture, microtexture, and Wheel Rut Dephts (RUT) through Sand Patch, British Pendulum, and Straightedge Gauge tests. The International Friction Index (IFI) was used to correlate results into a single index. ASTM classification helped not only categorize but also assess each analyzed point in relation to variables such as traffic, road geometry, age and wearing course type. It was observed that 60% of BR-101 segments and 19% of BR-235 require roadworks related to improvement of microtexture. However, the main cause of traffic accidents on these highways was the high traffic volume in urban segments. Additionally, predictive performance models adjusted for HS (texture depth) and IFI were proposed to estimate these variables over time, projecting the temporal deterioration of pavement texture and assisting decision-makers in roadworks planning.